LEVEL OF PHYSICAL ACTIVITY AND PHYSICAL FITNESS RELATED TO THE HEALTH OF ADOLESCENTS WITH DIFFERENT HABITS OF LEISURE (Fiep Bulletin - online, 2014)
The present work had as proposal to identify the main habits of adolescents' leisure, trying to observe if there were differences between the level of physical (NAF) activity and physical fitness related to the health (AFRS) of the same ones. For attainment of those objectives, the study used a questionnaire built starting from the Inventory of Habits of Leisure of Cloes et. al. (1997) adapted for Portuguese language by Esculcas & Mota (2005) and, of the Scale of Habits of Leisure developed by Ant, Ayroza & Dias (2005). To discover the level of physical activity the International Questionnaire of Physical Activity it was used. IPAQ, version tans (MATSUDO et. al., 2001) and, the physical fitness was evaluated through the protocol of PROESP-BR (GAYA, 2005). As methodological strategy of that work, we decided to classify the sample in two groups, G1 (apprentices of activities physics / sport in the moments of leisure) and, G2 (no apprentices of activities physics / sport in the moments of leisure). The results of the study showed that G1 presented larger frequency in leisure activities considered sedentary such as playing video it loves and to navigate in the internet, smaller sedentary levels and better physical fitness level. Those discoveries suggest that independently of the adolescent be involved in activities of sedentary leisure, the fact of the same to dedicate a part of his/her time for practice of physical activity, it is shown efficient to drive them to improve their indexes of AFRS, however the work also suggests that those objectives seem to be better reached with the accomplishment of the physical exercise, that with the practice of the physical activity, once G2 presented high activity levels and low AFRS.
Keywords: Leisure habits; Physical Activity; Physical fitness